2013
DOI: 10.1371/journal.pone.0059262
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Ancient Lepidopteran Lateral Gene Transfer

Abstract: Bacteria to eukaryote lateral gene transfers (LGT) are an important potential source of material for the evolution of novel genetic traits. The explosion in the number of newly sequenced genomes provides opportunities to identify and characterize examples of these lateral gene transfer events, and to assess their role in the evolution of new genes. In this paper, we describe an ancient lepidopteran LGT of a glycosyl hydrolase family 31 gene (GH31) from an Enterococcus bacteria. PCR amplification between the LG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 35 publications
0
82
0
Order By: Relevance
“…The examples discussed above (and two recent reports showing multiple ancient horizontal gene transfers from bacteria and fungi to the genomes of different lepidopteran species [61,62] and the genome of the crustacean Litopenaeus vannamei [63]) show that horizontal gene transfer in arthropods is no longer a curiosity and that more accurate screening of arthropod genomes and transcriptomes will surely unveil more evidence supporting the horizontal acquisition of genes in these metazoans.…”
Section: Horizontal Gene Transfer In Arthropodsmentioning
confidence: 99%
“…The examples discussed above (and two recent reports showing multiple ancient horizontal gene transfers from bacteria and fungi to the genomes of different lepidopteran species [61,62] and the genome of the crustacean Litopenaeus vannamei [63]) show that horizontal gene transfer in arthropods is no longer a curiosity and that more accurate screening of arthropod genomes and transcriptomes will surely unveil more evidence supporting the horizontal acquisition of genes in these metazoans.…”
Section: Horizontal Gene Transfer In Arthropodsmentioning
confidence: 99%
“…During analyses of the C. obscurior genome (Schrader et al, 2014), we identified prokaryotic scaffolds and candidates for horizontal gene transfers (HGTs) (Wheeler et al, 2013). These were then further characterized by blasting (blastx) all annotated genes against a database of prokaryotic proteins.…”
Section: Westeberhardia Detection and Phylogenomic Analysesmentioning
confidence: 99%
“…Here we exploit an ancient [19], facultative and prevalent [20][21][22][23][24][25][26] symbiosis between Lepidoptera and enterococci to reconcile these approaches by studying the role of host immunity and bacterial competition during metamorphosis within a single system. The gut microbiota of Lepidoptera is limited to a handful of bacterial species that varies with habitat and diet but often is dominated by enterococci that persist through metamorphosis [12].…”
Section: Introductionmentioning
confidence: 99%